Characterization of Plant Growth Promoting Rhizobacteria From Seasonal Flower Beds - Yeasmin , Rahana; Saha, Mihir Lal (Dhaka University Journal of Biological Sciences, 2023)
The present investigations were carried out to screen the PGPR isolates from five separate seasonal flower beds (Catharanthus roseus, Portulaca grandiflora, Celosia argentea, Gomphrena globosa and Impatiens balsamina) of Curzon Hall, University of Dhaka. The bacterial load of the collected soil samples ranged in between 7.60 ± 6.01 × 106 and 9.49 ± 5.44× 108 cfu/g, 5.34 ± 4.06×106 and 13.4 ± 4.8×106 cfu/g and 1.01 ± 0.59×106 and 1.19 ± 0.95×108 cfu/g on Nutrient Agar (NA), Luria-Bertani (LB) and Yeast Extract Mannitol Agar (YEMA), respectively. All the selected eight isolates were Gram positive and rod shaped. All isolates were found to be IAA producer and 7 showed varying levels of phosphate solubilizing activity. IAA production and phosphate (P) solubilization of the selected isolates ranged in between 9.76 ± 5.98 to 17.99 ± 1.865 U/ml, and 1.17 ± 0.59 to 1.84 ± 0.499 mg/l. Maximum production of both IAA and phosphate solubilization was achieved in 24h of incubation period at 37°C and pH 7.0. Germination test against Mung Bean (Vigna radiata) revealed positive plant growth promoting activities and could be used as PGPR inoculant. Dhaka Univ. J. Biol. Sci. 31(2): 321-328, 2022 (July)